Analysis Of MRI Knee Joint Examination In Meniscus Tear Case With STIR Sequence And T2 Medic Sagittal Cut At Radiology Installation Of Balimed Hospital Denpasar - Wahyu Jaya Andre Saputra; I Made Lana Prasetya; I Kadek Sukadana (Lembaga Pengembangan Kinerja Dosen, 2024)
Knee injuries are often encountered in general practice and in hospitals. One injury that can occur is injury to the meniscus which causes a meniscus tear. The meniscus is a fibro cartilage disc which is the content of the knee joint and is divided into two, namely the lateral meniscus and the medial meniscus. To confirm the diagnosis of injured ligaments is by carrying out an MRI examination. MRI examination of the knee joint using T2* Multi Echo Rechalled Gradient Echo can provide optimal images in cases of meniscus tears. MRI examination of the knee joint using MEDIC is very useful for cervical imaging, cartilage, joint and musculoskeletal examination. The advantage of the MEDIC sequence is that it can be used for 2D and 3D imaging and can reduce chemical shift artifacts. Based on the journal taken by the author, the sequence needed to clinically show a meniscus tear on an MRI Knee Joint examination is sagittal STIR and sagittal T2 MEDIC. then the most optimal sequence in clinically showing a meniscus tear is chosen to increase the efficiency of the examination time. The type of research used is qualitative research with a case study approach. The subjects used in this research were 3 Radiology Specialist Doctors and 3 Radiographers. The STIR and T2 MEDIC sequences on the MRI Knee Joint examination have their respective roles in confirming the diagnosis of Tear Meniscus. The STIR sequence plays a role in assessing the Anterior Cruriated Ligament, Posterior Cruriated Ligament, radiologists also want to see edema or swelling that occurs in the patient's genu. The MEDIC T2 sequence plays a role in assessing the medial and lateral meniscus, the radiologist also wants to see blood production in the patient's genu. The STIR and T2 MEDIC sequences in the MRI Knee Joint examination at the Balimed Denpasar Hospital installation are able to confirm the diagnosis, especially in the clinical Tear Meniscus, because with these two sequences, the picture of the Medial Meniscus, Lateral Meniscus, Anterior Cruriated Ligament, Posterior Cruriated Ligament, product blood and edema can be clearly seen.